Mortality of neonates born to mothers of extreme reproductive age in Ethiopia; multilevel mixed effect analysis of Ethiopian demographic and health survey data of 2016 - Tekeba, Berhan; Techane, Masresha Asmare; Workneh, Belayneh Shetie; Zegeye, Alebachew Ferede; Gonete, Almaz Tefera; Alemu, Tewodros Getaneh; Wassie, Mulugeta; Kassie, Alemneh Tadesse; Ali, Mohammed Seid; Mekonen, Enyew Getaneh; Tamir, Tadesse Tarik (Frontiers in Pediatrics, 2024)
Introduction Neonatal mortality is still a major public health problem in middle- and low-income countries like Ethiopia. Despite strategies and efforts made to reduce neonatal death, the mortality rate declines at a slower pace in the country. Though there are studies conducted on neonatal mortality and its determinants, our searches of the literature have found no study on the extent of mortality of neonates born to mothers of extreme reproductive age in the study area. Therefore, this study aimed to assess the magnitude and factors associated with the mortality of neonates born to mothers of extreme reproductive age in Ethiopia. Methods Secondary data analysis was conducted using 2016 Ethiopian Demographic and Health Survey data. The final study contained an overall weighted sample of 2,269 live births. To determine the significant factors in newborn deaths, a multilevel binary logistic regression was fitted. For measuring the clustering impact, the intra-cluster correlation coefficient, median odds ratio, proportional change in variance, and deviation were employed for model comparison. The adjusted odds ratio with a 95% confidence interval was presented in the multivariable multilevel logistic regression analysis to identify statistically significant factors in neonatal mortality. A P-value of less than 0.05 was declared statistically significant. Results The neonatal mortality rate of babies born to extreme aged reproductive women in Ethiopia was 34 (95% Cl, 22.2%–42.23%) per 1,000 live birth. Being twin pregnancy (AOR = 10; 95% Cl: 8.61–20.21), being from pastoralist region (AOR = 3.9; 95% Cl: 1.71–8.09), having larger baby size (AOR = 2.93; 95% Cl: 1.4–9.12) increase the odds of neonatal mortality. On the other hand, individual level media exposure (AOR = 0.3; 95% Cl: 0.09–0.91) and community level media exposure (AOR = 0.24; 95% Cl: 0.07–0.83), being term gestation (AOR = 0.14; 95% Cl: 0.01–0.81) decreases the odds of neonatal mortality born to mothers of extreme reproductive age. Conclusion Ethiopia had a greater rate of neonatal death among babies born at the extremes of reproductive age than overall reproductive life. Multiple pregnancies, larger baby sizes, emerging regions, term gestation, and media exposure were found to be significant factors associated with the mortality of neonates born to mothers of extreme reproductive age. Therefore, the concerned bodies should give emphasis to mothers giving birth before the age of 20 and above 35, access to media, healthy pregnancy, and special attention to pastoralists to reduce the burden of neonatal mortality.